Gestión de riesgos físicos y mecánicos en el área de producción de la compañía Agua Santa Aliaguasanta Cía Ltda. - Tejada Martínez, Nicolle Yelena (2024)
Amidst a fiercely competitive sausage market, the Agua Santa Aliaguasanta Food Company CÍA. LTDA. distinguishes itself with its specialized focus on the production, conservation, storage, and distribution of sausages and meats, primarily catering to the local market in the country's central region. The company's commitment to standardized processes, technology, and continuous improvements in its production lines, while commendable, has led to the emergence of certain physical and mechanical risks, such as machinery manipulation and departmental order, among others. An information gathering was carried out for the initial identification of risks in the company's production area through the implementation of surveys and the observation technique; in addition, a qualitative measurement of physical and mechanical risks was carried out using a Qualitative Compliance Checklist and the tabulation of the surveys applied, since equipment for precise quantitative measurements was not available. William T. Fine's methodology was used to evaluate physical and mechanical risk factors, identifying two notable risks in the grinding and mixing areas that require immediate correction and twenty-eight moderate risks for which preventative measures are suggested. Finally, an Action Plan detailing corrective and preventive control measures to minimize and reduce these 30 risk factors is detailed. In total, the rest of the evaluated risks were considered acceptable and under control. One hundred twenty-six risk factors were identified throughout the production department.